2022
DOI: 10.1002/glr2.12008
|View full text |Cite|
|
Sign up to set email alerts
|

Photothermal controls of vegetative dormancy in Poa secunda

Abstract: Background Summer vegetative dormancy is a desirable trait in cool‐season grasses when they are interplanted with annual crops. Sandberg bluegrass (Poa secunda J. Presl.) shows summer dormancy, but the environmental cues that control dormancy remain unknown. Methods A controlled environment study using temperature and day length combinations of 32.2°C/15 h, 26.6°C/14 h, 21.1°C/13 h, and 15.5°C/12 h was conducted with P. secunda accessions PI232347, PI639272, and PI232348, and ‘Audubon’ red fescue as a nondorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This further emphasizes the potential importance and strength of the drought dormancy strategy for this species (and for this system). Recent work has also shown that P. secunda may enter and break dormancy in response to temperature and photoperiod (potentially more than soil moisture, Chen et al., 2022). Past work in this same experiment (Bio3D) demonstrated how P. secunda can shift energy allocation to invest more in roots at the expense of shoots in combined soil drying and atmospheric drying conditions (Watson et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This further emphasizes the potential importance and strength of the drought dormancy strategy for this species (and for this system). Recent work has also shown that P. secunda may enter and break dormancy in response to temperature and photoperiod (potentially more than soil moisture, Chen et al., 2022). Past work in this same experiment (Bio3D) demonstrated how P. secunda can shift energy allocation to invest more in roots at the expense of shoots in combined soil drying and atmospheric drying conditions (Watson et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This further emphasizes the potential importance and strength of the drought dormancy strategy for this species (and for this system). Recent work has also shown that P. secunda may enter and break dormancy in response to temperature and photoperiod (potentially more than soil moisture, Chen et al, 2022) F I G U R E 3 Nonmetric dimensional scaling (NMDS) ordination of Bray-Curtis dissimilarity among the grass communities under three levels of humidity in dry soils (shades of red) and three levels of humidity in wet soils (shades of blue, k = 3; stress = 0.1; PERMANOVA, interaction term pseudo-F 1,18 = 1.77, r 2 = .2, p = .09). Species labels are located on the ordination based on their species scores and rescaled for visualization with pot communities.…”
Section: Soil Drought: Community Compositionmentioning
confidence: 99%